1997
DOI: 10.1002/(sici)1097-0339(199701)16:1<17::aid-dc5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous needle biopsy diagnosis of benign neurogenic neoplasms

Abstract: Preoperative diagnosis of benign neurogenic neoplasms (BNNs) provides useful information in guiding management. To assess the effectiveness of fine‐needle aspiration (FNA) and needle core biopsy (NCB) in diagnosing schwannomas and neurofibromas, 40 percutaneous biopsies interpreted as BNNs or obtained from lesions subsequently shown by excision to be BNNs were reviewed. The 13 aspirates diagnostic of BNN revealed spindle cells arranged haphazardly in irregular tissue fragments and in parallel as elongated ropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 6 publications
0
27
2
Order By: Relevance
“…2,3,7,15 However, in 28 cases with satisfactory specimens in the present study, the sensitivity was 64.3% (18/28), which represents an acceptable diagnostic performance. These results were similar to those of previous studies that evaluated FNAC for the diagnosis of schwannoma, which reported unsatisfactory specimen rates of 36%-50% and sensitivity rates of 0%-40%.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…2,3,7,15 However, in 28 cases with satisfactory specimens in the present study, the sensitivity was 64.3% (18/28), which represents an acceptable diagnostic performance. These results were similar to those of previous studies that evaluated FNAC for the diagnosis of schwannoma, which reported unsatisfactory specimen rates of 36%-50% and sensitivity rates of 0%-40%.…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, obtaining an accurate preoperative diagnosis, preferably while identifying the nerve of origin, is critical for establishing an appropriate management plan for this type of tumor. 3,7 Moreover, immunohistochemical staining, which is usually critical for the diagnosis of schwannoma, is unavailable for cytological specimens harvested using FNAC. 5,6 Although this technique is easily available and highly accurate for most head and neck masses, the diagnostic sensitivity of FNAC for schwannomas is relatively low at 0%-40%, and also too often produces unsatisfactory specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirates from neurofibroma are frequently nondiagnostic . The current series contained a single atypical neurofibroma.…”
Section: Discussionmentioning
confidence: 85%
“…Distinguishing low‐grade malignant peripheral nerve sheath tumor may be challenging, even after surgical resection has been performed. On FNAB material, cellular dissociation is a helpful diagnostic feature, because it is observed for the most part in malignant tumors . If adequate tissue is available, the presence of diffuse and intense immunoreactivity for S‐100 protein or SOX10 is also useful, because spindle cell malignant peripheral nerve sheath tumors rarely exhibit strong S‐100 protein or SOX10 reactivity …”
Section: Discussionmentioning
confidence: 99%
“…In the anatomic region of the hand, cytologically we have occasionally mistaken leiomyomas for schwannomas and dermatofibromas, and we have missed neurofibromas. Resnick et al 27 pointed out the low sensitivity of cytology in the recognition of benign neurogenic tumors.…”
Section: Fna Of Hand Lesionsmentioning
confidence: 99%